Prospection and Characterization of Essential Oil from Peels, Seeds, and Leaves of Litchi chinensis Sonn. - Patrícia Graosque Ulguim Züge; Sarita Leonel; Jordany Aparecida de Oliveira Gomes; Júlio César Rodrigues Lopes Silva; Marcia Ortiz Mayo Marques (Brazilian Archives of Biology and Technology)
Abstract The essential oils extracted from plants can demonstrate biological activity against a significant number of pathogens and/or antioxidant activity. The objective was to extract and identify the substances present in the essential oil of leaves, peel, and seeds of 'Bengal' lychee. Leaves and fruits of Litchi chinensis Sonn. were collected from an orchard located at the São Manuel Experimental Farm, Faculty of Agronomic Sciences at the São Paulo State University (FCA/Unesp/Brazil). The extraction of the essential oil was performed by hydrodistillation using a Clevenger-type apparatus. The analysis of the essential oil was carried out using gas chromatography coupled with a mass spectrometer and a flame ionization detector. The qualitative and quantitative analyses of the chemical composition and the yield of essential oil were performed in triplicate, and the data were subjected to multivariate analysis. The essential oil yield ranged from 0.03% to 0.19%, with the highest percentage observed in the lychee peel. Twenty-two compounds were identified in the leaf, eighteen in the peel, and twenty in the seed. γ-Himachalene was the most abundant in the essential oil of the leaf, peel, and seed, with 30.36%, 51.85%, and 39.95%, respectively. The essential oil of lychee contains compounds with potential for use in various industrial sectors.